Aprotinin Impacts 8-Isoprostane after Coronary Artery Bypass Grafting. (December 2018) - Toikkanen, V.; Rinne, T.; Nieminen, R.; Moilanen, E.; Laurikka, J.; Porkkala, H.; Tarkka, M.; Mennander, A. A.
Background and Aims: The lungs participate in the modulation of the circulating inflammatory factors induced by coronary artery bypass grafting. We investigated whether aprotinin—which has been suggested to interact with inflammation—influences lung passage of key inflammatory factors after coronary artery bypass grafting. Material and Methods: A total of 40 patients undergoing coronary artery bypass grafting were randomized into four groups according to aprotinin dose: (1) high dose, (2) early low dose, (3) late low dose, and (4) without aprotinin. Pulmonary artery and radial artery blood samples were collected for the evaluation of calculated lung passage (pulmonary artery/radial artery) of the pro-inflammatory factors interleukin 6 and interleukin 8, 8-isoprostane, myeloperoxidase and the anti-inflammatory interleukin 10 immediately after induction of anesthesia (T1), 1 min after releasing aortic cross clamp (T2), 15 min after releasing aortic cross clamp (T3), 1 h after releasing aortic cross clamp (T4), and 20 h after releasing aortic cross clamp (T5). Results: Pulmonary artery/radial artery 8-isoprostane increased in patients with high aprotinin dose as compared with lower doses (1.1 range 0.97 vs 0.9 range 1.39, p = 0.001). The main effect comparing high aprotinin dose with lower doses was significant (F(1, 38) = 7.338, p = 0.01, partial eta squared = 0.16) further supporting difference in the effectiveness of high aprotinin dose for pulmonary artery/radial artery 8-isoprostane. Conclusion: According to the pulmonary artery/radial artery equation, the impact of aprotinin on 8-isoprostane after coronary artery bypass grafting is dose dependent. Aprotinin may aid the lung passage of circulating factors toward a beneficial anti-inflammatory milieu.